Algorithm Advanced Control Chaos and Stabilization Measurement Error. (August 2019) - Wanayumini,; Zarlis, Muhammad; Suwilo, Saib; Furqan, Mhd.; Fauzi, Rahmat; Syarifah, Tengku
Abstract: Measurement error in the data sample human voice from the data 1 to 17 obtain measurement results with the algorithm Advanced Chaos Control and Stabilization through several stages of delivery of the process control and and stabilizing the data to find the value of noise and bias in the initial process control and find the value of precision and accuracy in both the stabilization process. Stable value which must be controlled ranging 58, 9922dB and 60, 47059dB with a standard value of 60dB.